Socio-demographic profile and reasons for previous partial and unimmunization among children attending Mission Indradhanush session: a cross sectional study - R., Chandrashekhar; Basagoudar, Shashidhar S.; Hatnoor, Shivappa; Kirte, Rahul C. (International Journal Of Community Medicine And Public Health, 2018)
Background: In December 2014, Ministry of Health and Family Welfare of India launched Mission Indradhanush with the aim to ensure that all children are fully vaccinated against seven vaccine-preventable diseases before they reach an age of two years. Methods: A cross sectional, community based study was conducted among parents attending Indradhanush Vaccination Centre (IVC) along with their partial and unimmunized children aged 0-23 months. Study was conducted during Mission Indradhanush (MI) 2nd Phase from November 2015 to January 2016. Data consisting of information regarding the various demographic variables, immunization history, and reasons for partial and unimmunization was collected by interviewing the parents through a pre-tested, structured questionnaire. Results: A total of 153 children were studied involving 63 session sites. 50 (32.7%) children were residing in low coverage areas, 4 (2.6%) children in villages with migratory population, 4(2.6%) children in areas with missed session and 87(56.9%) children residing in village with vacant sub centre. Common reasons for not vaccination were, child was sick on the day of vaccination (32%), child migrated to other place (27.5%), Fear of AEFI (11.8%), ignorance (11.1%). Only 92 (60.1%) children were having MCP card. Conclusions: The reasons for partial and un immunization were mainly lack of awareness of parents, sickness of children, fear of AEFI and migration to other places which would be solved by taking all efforts to raise the awareness of community about need of immunization along with providing complete information about the immunization services being provided to them.